Granular cell tumor of the urinary bladder: A case report (Indian Journal of Case Reports, 2018)
Granular cell tumors (GCTs) are the tumors arising from Schwann cells. They should be considered as one of the differential diagnosis in the solid tumors of the bladder. Here, we report the case of a 60-year-old female presented with lower abdominal pain and burning micturition who on evaluation with contrast-enhanced computed tomography was found to have a bladder mass of 4 cm × 3 cm in the left lateral wall. Cystoscopy showed a smooth ovoid mass 4 cm × 3 cm situated above and lateral to the left ureteric orifice covered by normal bladder mucosa. The patient underwent transurethral resection of the bladder tumor, which was diagnosed as a GCT on histopathological examination and immunohistochemistry.